Synthesizing Empirical and Modelling Studies to Predict Past and Future Primary Production in the North Sea - Spence, Michael A.; Lynam, Christopher P.; Thorpe, Robert B.; Heneghan, Ryan F.; Dolder, Paul J. (Frontiers in Marine Science, 2022)
Understanding change at the base of the marine foodwebs is fundamental to understanding how climate change can impact fisheries. However, there are a shortage of empirical measurements of primary productivity, and models estimates often disagree with each other by an order of magnitude or more. In this study we incorporate information from empirical studies and a suite of Earth system models statistically downscaled using an ensemble model to produce estimates of North Sea primary production with robust quantification of uncertainties under two different climate scenarios. The results give a synthesised estimate of primary production that can feed into regional fisheries models. We found that Earth system models describe the dynamics of primary production in the North Sea poorly, and therefore the effects of climate change on future primary production is uncertain. The methods demonstrated here can be applied to other geographical locations and are not limited to primary production.